Factors Influencing Adolescent Girl's Compliance in Consuming Iron Tablet Supplementation in Rural Areas in Indonesia - Hasti Savira Yudiana; Hashfi Khairuddin (Universitas Malahayati Lampung, 2025)
ABSTRACT Anaemia is common among adolescent girls due to the accelerated growth and development of their bodies during puberty, which necessitates sufficient nutritional intake. In addition, young women also undergo menstruation, which results in significant monthly blood loss, hence doubling the requirement for iron during this period. According to the 2018 Ministry of Health research findings, 76.2% of teenage girls have been given iron tablet supplements. However, out of this group, only 1.4% of teenage girls have taken 52 or more iron tablet supplements. Therefore, there is still a significant number of teenage girls who are experiencing anaemia. Discover the level of compliance to iron tablet supplementation among young women and the factors that impact it in the rural areas of Indonesia, specifically in Kersaratu Village, Malingping District. The investigation will employ descriptive methodologies. The population for this study comprised all 22 students in the seventh grade at Malingping 3 Junior High School. The research sample comprised 12 female students who were in the 7th grade at Malingping 3 Junior High School and matched the specified inclusion criteria. The sample approach was conducted utilising the method of total sampling. The data collected from participants' responses to the questionnaire were subsequently processed and analysed using the SPSS 26.0 software. Based on the examination results, Malingping 3 Junior High School had a total of 12 female students with anaemia at the initial visit. Among them, 7 individuals (58.3%) had mild anaemia, while 5 individuals (41.7%) had moderate anaemia. During the second visit, there was a notable decrease in the number of female students who had anaemia, with only one student (8.3%) still experiencing this condition. During the initial visit, the compliance score was relatively low, with just 41.7% of female students adhering to the recommended iron tablet supplementation. During the second visit, the level of compliance rose to 58.3%. Out of the total number of students, specifically eight female students, which accounts for 66.7% of the group, demonstrated a commendable degree of understanding of anaemia. According to the survey, 75% of female students reported receiving assistance from teachers in taking iron tablet supplements, whereas only 25% reported receiving support from their parents. The level of compliance with the consumption of iron tablet supplementation among young women is mostly influenced by the quality of teacher support. Adhering to a regular intake of iron tablet supplements can have a significant impact on the anaemia status of young women. Keywords: Anemia, Adolescent Girls, Management, Factors, Rural